2021
DOI: 10.1161/str.52.suppl_1.p597
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P597: Growing Prevalence of Post-Stroke Sleep-Disordered Breathing

Abstract: Introduction: Sleep-disordered breathing (SDB) is common after stroke and is associated with poor functional and cognitive outcomes, and recurrent stroke. Despite increasing prevalence of SDB in the general population, no data are available about trends in post-stroke SDB. We therefore sought to assess changes in post-stroke SDB prevalence over a 10-year period. Methods: Within the Brain Attack Surveillance In Corpus Christi (BASIC) project, a populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Individuals with OSA often present clinical symptoms such as sleepiness, fatigue, and headache [ 1 ]. The incidence of OSA in stroke patients increased from 61% in 2011 to 75% in 2019 [ 2 4 ], a rate significantly higher than the 35% found in the general population [ 5 ]. Previous studies found that OSA was associated with prolonged hospital stay, increased recurrence of stroke, and elevated mortality rates among stroke patients [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with OSA often present clinical symptoms such as sleepiness, fatigue, and headache [ 1 ]. The incidence of OSA in stroke patients increased from 61% in 2011 to 75% in 2019 [ 2 4 ], a rate significantly higher than the 35% found in the general population [ 5 ]. Previous studies found that OSA was associated with prolonged hospital stay, increased recurrence of stroke, and elevated mortality rates among stroke patients [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%